Clean label extraction of bioactive compounds from Chenopodium album and their role in the characterization and stability of ostrich meat - Khalid, Muhammad Zubair; Saima, Hafiza; Nadeem, Muhammad Tahir; Saeed, Kanza; Arshad, Muhammad Sajid; Khalid, Waseem; Rafique, Hamad; Fatima, Muqaddas; Alsulami, Tawfiq; Alzahrani, Abdulhakeem (Frontiers in Sustainable Food Systems, 2024)
The demand for clean-label products continues to rise, as consumers increasingly prioritize natural and transparent ingredient lists. Natural substances are generally deemed safe for consumption by consumers. This study was focused on the development of clean-label ostrich meat patties with Chenopodium album extract and their storage stability. To prepare C. album extract, microwave-assisted extraction (MAE) and ultrasound-assisted extraction (UAE) were employed. Ostrich meat patties were prepared using diverse combinations of extract, including 1% UAE, 2% UAE, 1% MAE, 2% MAE, 0.5% UAE+0.5% MAE, and 1% UAE + 1% MAE. The highest pH was observed for MAE in T3 on the 14th day (6.19 ± 0.03). The L* value was observed between 39.12 ± 1.09 and 44.00 ± 1.1. As storage intervals passed, the a* and b* values of ostrich meat patties decreased. After the 14th day of storage, the best results were obtained from 2% UAE (T2), with the lowest TBRAS, Peroxide value (POV), and Total of volatile basic nitrogen (TVBN) readings recorded for T2 (0.74 ± 0.02 MDA/kg, 0.56 ± 0.01 meq peroxide/kg, and 6.28 ± 0.40 mg/100 mL, respectively). At the end of the storage study, the lowest Total Microbial Count (TMC) and coliform count were recorded for T2 (8.08 ± 0.03 and 4.97 ± 0.05 cfu/mL, respectively). At the end of the storage study, T2 exhibited the highest values for total phenolic content (TPC), diphenyl-1-picrylhydrazyl (DPPH), Ferric reducing antioxidant power (FRAP), and azino-bis-3-ethylbenzothiazoline-6-sulfonic acid (ABTS) assay, namely of T2 122 ± 0.28 mg GAE/100 g, 73 ± 0.27%, 5.9 ± 0.01 mmol FSE/100 g, and 83 ± 0.08 mmol/L, respectively. The current study concludes that the UAE extract of C. album incorporated into ostrich meat patties manifests improved safety, quality, and storage stability. The implementation of clean label strategies can facilitate food manufacturers to align with consumer preferences for product transparency and sustainability while ensuring product safety and quality.